Atomoxetine and citalopram alter brain network organisation in Parkinson's disease. Issue 6 (27th May 2022) - Borchert, Robin; Rittman, Timothy; Rae, Charlotte; Passamonti, Luca; Jones, Simon; Vatansever, Deniz; Rodríguez, Patricia Va´zquez; Ye, Zheng; Rowe, James; ,
Abstract : Recent evidence has shown potential cognitive benefits in Parkinson's disease from restoring neuro- transmitter deficits including noradrenergic and serotonergic transmission. Here, we study global and regional brain network organization using task-free imaging, which minimizes performance confounds and the bias towards predetermined networks. Thirty-three patients with idiopathic Parkinson's disease were studied three times in a double-blinded, placebo-controlled crossover design, following placebo, 40mg oral atomoxetine or 30mg oral citalopram. Seventy-six controls were scanned without medication to provide normative data. Relative to controls, patients on placebo had executive impairments, which was reflected in dysfunctional network dynamics in terms of reduced clustering coefficient, hub degree and hub centrality. In patients, atomoxetine improved fluency in proportion to plasma concentration (P=0.006, r2=0.24), and improved response inhibition in proportion to increased hub Eigen centrality (P=0.044, r2=0.14). Citalopram did not improve fluency or inhibitory control, but its influence on network integration and efficiency depended on disease severity: clustering (P=0.01, r2=0.22), modularity (P=0.043, r2=0.14) and path length (P=0.006, r2=0.25) increased in patients with milder forms of Parkinson's disease, but decreased in patients with more advanced disease (UPDRSIII>30). This study supports the use of task-free imaging of brain networks in translational pharmacology of neurodegenerative disorders. We propose that hub connectivity contributes to cognitive performance in Parkinson's disease, and that noradrenergic treatment strategies can partially restore the neural systems supporting executive function. robinborchert@gmail.com